Molecular genetic typing of Staphylococcus aureus from cows, goats, sheep, rabbits and chickens - Smyth, Davida S. (Trinity College (Dublin, Ireland). Department of Microbiology, 2006)
Staphylococcus aureus is an important pathogen of man causing a range of infections from boils, carbuncles and abscesses to more serious and life-threatening infections like endocarditis and osteomyelitis. S. aureus is also an important pathogen of animals. Bovine mastitis is one of the most important infectious diseases among dairy cattle worldwide resulting in several billion dollars of lost revenue to the dairy industry every year, with S. aureus being a common cause. Apart from mastitis in cows, sheep and goats, S. aureus can cause septicaemia, lameness and skeletal infections such as osteomyelitis in commercial broiler flocks. In rabbits S. aureus can infect small dermal lesions and invade subcutaneous tissue causing staphylococcosis.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin